2011
DOI: 10.1007/s00221-011-2635-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight-related labels on corticospinal excitability during observation of grasping: a TMS study

Abstract: Recent studies of corticospinal excitability during observation of grasping and lifting of objects of different weight have highlighted the role of agent's kinematics in modulating observer's motor excitability. Here, we investigate whether explicit weight-related information, provided by written labels on the objects, modulate the excitability of the observer's motor system and how this modulation is affected when there is a conflict between label and object's weight. We measured TMS-evoked motor potentials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 36 publications
7
53
0
Order By: Relevance
“…Thus, we observed that, once the actual weight of the object became known in the deceived condition, the FDI muscle was involved in adjusting the lifting of the object according to its actual weight. In particular, in the central and last phases of truthful lifting, the FDI muscle was more activated for the heavy than for the light object (third bin: P = 0.023; fourth bin: P < 0.001; fifth bin: P < 0.001), in keeping with the sensitivity of the hand muscles to object weight (Alaerts et al 2010a(Alaerts et al , 2010bSenot et al 2011;Tidoni et al 2013). Importantly, this weight-sensitivity was reflected into a reduced activation of the FDI while the actors were lifting an object that was expected to be lighter than its actual weight as compared to when they received truthful information.…”
Section: Emg Data During Action Executionmentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, we observed that, once the actual weight of the object became known in the deceived condition, the FDI muscle was involved in adjusting the lifting of the object according to its actual weight. In particular, in the central and last phases of truthful lifting, the FDI muscle was more activated for the heavy than for the light object (third bin: P = 0.023; fourth bin: P < 0.001; fifth bin: P < 0.001), in keeping with the sensitivity of the hand muscles to object weight (Alaerts et al 2010a(Alaerts et al , 2010bSenot et al 2011;Tidoni et al 2013). Importantly, this weight-sensitivity was reflected into a reduced activation of the FDI while the actors were lifting an object that was expected to be lighter than its actual weight as compared to when they received truthful information.…”
Section: Emg Data During Action Executionmentioning
confidence: 57%
“…These 2 muscles were selected for their motor role during reaching-tograsp and lifting movements and sensitivity to genuine versus deceptive intentions during action observation. Indeed, the FDI muscle activity is directly involved in controlling the strength of the grip during lifting (Alaerts et al 2010a(Alaerts et al , 2010bSenot et al 2011). More importantly, the FDI CSE is more facilitated during the observation of fooling than genuine hand actions exerted upon objects of the same weight (Tidoni et al 2013).…”
Section: Tms and Electromyographymentioning
confidence: 99%
“…These authors demonstrated that observing error-free lifts of heavy-looking stimuli evokes larger motor potentials than observing lifts of light-looking stimuli. Subsequent research demonstrated that this effect appears to be driven by kinematic differences in the way that light and heavy objects are lifted, rather than differences in how heavy they look simply on the basis of their apparent static weight (Alaerts et al, 2009;Senot et al, 2011). In the current work, when comparing the EV to the NEV when object size was held constant, we noted that the EV and the NEV elicited similar MEPs for the small cube (t(17) = 0.66, p=.52).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the underestimations of force that were applied to the small cube give it the kinematics of a heavier object (see Supplementary Video 1). It has been convincingly demonstrated that observing such easy-and difficult-looking lifting kinematics can in fact modulate cortico-spinal activity such that observing lifts that look effortful will elicit larger MEPs than observing easy-looking lifts (Senot et al, 2011). It is likely that these kinematic-based modulations in cortico-spinal excitability oppose the size-based effects seen in the no error video, leading to the similar MEPs when watching error-filled lifts of large and small cubes (see also Obhi and Hogeveen, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation